Involvement of α 1-2-fucosyltransferase I (FUT1) and surface-expressed lewisy (CD174) in first endothelial cell-cell contacts during angiogenesis - Möhler, Thomas; Sauer, Sandra; Witzel, Maximilian G. W.; Andrulis, Mindaugas; Garcia-Vallejo, Juan J.; Grobholz, Rainer; Willhauck-Fleckenstein, Martina; Greiner, Axel; Goldschmidt, Hartmut; Schwartz-Albiez, Reinhard (Journal of cellular physiology, 2008)
During the initiation of tumor associated angiogenesis endothelial cells migrate, adhere to extracellular matrix and form cell-cell contacts. Humoral factors of malignant cells conduct this process. We investigated whether cell surface expression of the carbohydrate blood group determinant Lewisy (CD174) and its precursor structure H2 (CD173) on endothelial cells is influenced by soluble factors of tumor cells. Using a bone marrow derived endothelial cell line we observed an enhanced expression of CD173/CD174 and transcription of FUT1, the key enzyme for their synthesis, after treatment with tumor necrosis factor-α (TNF-α) or conditioned supernatants of the leukemia cell line KG1a. CD173/CD174 are concentrated on pseudopodial extensions responsible for initial contacts between endothelial cells. Endothelial migration induced by TNF-α could be diminished by antibodies to CD174 as well as by siRNA induced downmodulation of FUT1 transcription. Endothelial FUT1-siRNA-transfectants displayed impaired in vitro angiogenesis when cultivated on extracellular matrix and in spheroid assays. In vivo upregulation of CD174 expression was observed immunocytologically in capillaries of tumor-infiltrated tissue. Together, our observations point to a tumor induced transcription of endothelial FUT1 and consequently an enhanced expression of CD174 which is involved in migration and early cell-cell contacts during tumor associated angiogenesis. J. Cell. Physiol. 215: 27-36, 2008. © 2008 Wiley-Liss, Inc.